Heart Failure With Preserved Ejection Fraction Phenotype Is Associated With Early Symptom Onset in Aortic Stenosis and Residual Symptoms After Transcatheter Aortic Valve Implantation - Constantijn S. Venema; Kees H. van Bergeijk; Jan A. Krikken; Hindrik W. van der Werf; Ad F. M. van den Heuvel; Yvonne L. Douglas; Ify R. Mordi; Nicolas Girerd; Chim C. Lang; Carolyn S. P. Lam; Martin B. Leon; Erik Lipsic; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Aortic stenosis can lead to cardiac adaptations and symptoms similar to heart failure with preserved ejection fraction. We hypothesized that a heart failure with preserved ejection fraction phenotype in aortic stenosis is associated with earlier onset of symptoms and reduced symptomatic response after transcatheter aortic valve implantation (TAVI). Methods and Results This retrospective cohort study included 469 patients with moderate aortic stenosis. We determined heavy, hypertension, atrial fibrillation, pulmonary, elder, filling pressure (H2FPEF) score at diagnosis and compared aortic peak jet velocity at onset of dyspnea in patients with low (<6) and high (≥6) H2FPEF score. In a separate cohort of 601 patients undergoing TAVI, we compared New York Heart Association class, NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), and cardiovascular mortality post‐TAVI between patients with low and high H2FPEF scores. In patients with aortic stenosis and a high H2FPEF score (n=43, 9.2%), the median peak jet velocity at onset of dyspnea was 4.2 versus 4.4 m/s in patients with a low H2FPEF score (P<0.001). After TAVI, a high H2FPEF score (n=123, 20%) was associated with a lower proportion of New York Heart Association class I at 30 days (49% versus 61%; P=0.04), persistently elevated NT‐proBNP, and higher 5‐year rate of cardiovascular mortality (36% versus 30%; P=0.012), compared with a low H2FPEF score. Conclusions Patients with aortic stenosis with a heart failure with preserved ejection fraction phenotype are more likely to develop symptoms at lower gradients and have worse outcomes post‐TAVI. Randomized trials are warranted to investigate whether medical therapy targeted at heart failure with preserved ejection fraction delays onset of symptoms and improves symptomatic response after TAVI.